Addition of 1, 3-dicarbonyl compounds to terminal alkynes catalyzed by a cationic cobalt(iii) complex. Issue 59 (30th September 2020) - Chandra Sau, Mohan; Bhattacharjee, Manish
Abstract : The Nakamura reaction using the complex, [Cp*Co(CH3 CN)3 ][SbF6 ]2 as the catalyst has been described. Alkynes on reaction with β-ketoesters afford tetrasubstituted benzenes. Abstract : The Nakamura reaction using a cationic cobalt(iii ) complex, [Cp*Co(CH3 CN)3 ][SbF6 ]2 as the catalyst under neutral and aerobic conditions at 110 °C has been described. In solution, the complex is expected to lose a hemilabile acetonitrile ligand to produce a highly electron-deficient cobalt(iii ) center, and the Lewis acidic nature of the cobalt center has been exploited for the enolization of the dicarbonyl compounds. The reaction of 1, 3-dicarbonyl compounds with alkynes affords the corresponding alkenyl derivative. However, the reaction of phenylacetylene and its derivatives with β-ketoesters affords corresponding terphenyl compounds. Details of the mechanisms of the reactions have been proposed based on in situ LCMS measurements.